Side Effects of Coronary Stenting such as Severe Coronary Stenosis and Multiple Coronary Chronic Total Occlusions in Elderly Patients via Induced Proinflammatory and Prooxidative Stress - Li, Xia; Guo, Dianxuan; Zhou, Hualan; Hu, Youdong; Fang, Xiang; Chen, Ying; Zhang, Fenglin (Mediators of Inflammation, 2019)
Background. Severe coronary stenosis and multiple coronary chronic total occlusions are serious side effects of coronary stent implantation in elderly patients. This research sought to investigate the side effects of coronary stenting such as severe coronary stenosis and multiple coronary chronic total occlusions in elderly patients via induced proinflammatory and prooxidative stress. Methods. We evaluated the expression levels of tumor necrosis factor-α (TNF-α), toll-like receptor 4 (TLR4), acrolein (ACR), malondialdehyde (MDA), high-sensitivity C-reactive protein (hs-CRP), stromal cell-derived factor-1α (SDF-1α), superoxide dismutase 3 (SOD3), and endothelial nitric oxide synthase (eNOS) in elderly patients with severe coronary stenosis and multiple coronary chronic total occlusions. Results. Levels of TNF-α, TLR4, ACR, MDA, and hs-CRP were remarkably increased (P<0.001), and levels of SDF-1α, SOD3, and eNOS were remarkably lowered (P<0.001) in elderly patients with severe coronary stenosis and multiple coronary chronic total occlusions. Coronary stenting induced proinflammatory and prooxidant mediator expression and inhibited anti-inflammatory/antioxidant mediators. The proinflammatory and prooxidant mediators may be involved in severe coronary stenosis and multiple coronary chronic total occlusions in elderly patients. Conclusions.Side effects such as severe coronary stenosis and multiple coronary chronic total occlusions because of coronary stenting in elderly patients were induced by proinflammatory and prooxidative stress. Circulating proinflammatory and prooxidant mediators could predict early severe coronary stenosis and multiple coronary chronic total occlusions in elderly coronary heart disease patients.